Development of the “Masgapur” Thematic Storybook Based on the Pancasila Village Model to Enhance Religious Tolerance and Moderation in Early Childhood - Yuseptina, Titin; Arifin, Imron; Dian Putra, Yudithia (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study develops and evaluates the Masgapur thematic picture storybook as a learning medium to strengthen religious tolerance and moderation among early childhood learners. Rooted in the socio-cultural context of a “Pancasila Village,” the storybook presents harmonious interactions among children from different religious backgrounds Islam, Christianity, and Hinduism symbolized through Masgapur (Masjid, Gereja, Pura). Employing the ADDIE model, the research followed five stages: needs analysis, design, development, implementation, and evaluation. Data were obtained through observations, interviews with teachers and parents, expert validation in early childhood education, media design and linguistics, and pre-test and post-test assessments. Needs analysis revealed limited access to culturally relevant storybooks that integrate local values and multilingual elements. The developed storybook features simple narratives, contextual illustrations, and local cultural values aligned with Pancasila principles of unity and mutual respect. Expert validation indicated high feasibility with scores above 85% across all categories. Small- and large-group trials demonstrated strong child engagement and understanding of multicultural content. Post-test results showed a 38.9% improvement in children’s tolerance and religious moderation skills. Overall, the Masgapur storybook is pedagogically feasible and effective, underscoring the value of integrating local wisdom, narrative-based learning, and character education to promote peaceful coexistence in early childhood settings.